2020
DOI: 10.7717/peerj-cs.284
|View full text |Cite
|
Sign up to set email alerts
|

Lean thinking by integrating with discrete event simulation and design of experiments: an emergency department expansion

Abstract: Background Many management tools, such as Discrete Event Simulation (DES) and Lean Healthcare, are efficient to support and assist health care quality. In this sense, the study aims at using Lean Thinking (LT) principles combined with DES to plan a Canadian emergency department (ED) expansion and at meeting the demand that comes from small care centers closed. The project‘s purpose is reducing the patients’ Length of Stay (LOS) in the ED. Additionally, they must be assisted as soon as possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Other less reported tools included process capability, regressions, and design of experiments (DOE). In fact, DOE has been reported as one of the main tools within six sigma [172]; however, in this research, only one study reported the DOE utilization [37]. This absence might be due to simulation replacing trials in processes where real experimentation is difficult.…”
Section: Lss Tools Utilized In the Interventionsmentioning
confidence: 69%
See 1 more Smart Citation
“…Other less reported tools included process capability, regressions, and design of experiments (DOE). In fact, DOE has been reported as one of the main tools within six sigma [172]; however, in this research, only one study reported the DOE utilization [37]. This absence might be due to simulation replacing trials in processes where real experimentation is difficult.…”
Section: Lss Tools Utilized In the Interventionsmentioning
confidence: 69%
“…Notably, the dual intervention of improvement approaches (lean, SS, and LSS) and simulation in healthcare has increased in recent years. For instance, lean and system dynamic (SD) simulation for an ICU re-design [35]; just-in-time approach and simulation for inventory management of surgical instruments in operating rooms (OR) [36]; LSS and simulation for reducing the patients' length of stay in the ED [37]; transforming an ED workflow combining lean, machine learning, and simulation [7]; or reducing waiting time through system dynamics and value stream map [27] have not only demonstrated the possibility but also the practicality of dual interventions. Despite the increasing popularity and adoption of LSS and simulation, not all organizations have reported successful outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The specialists and the modeling team analyzed the simulated model. They agreed that it was as close to the actual patient flow as possible, and then experiments were performed to reduce patients’ waiting time and standardize it [ 63 ].…”
Section: Research Problems Approaches and Applied Toolsmentioning
confidence: 99%
“…However, results show such systems do not fit for stream fluctuation and uneven workload distribution. Semeniuta & Falkman (2019) and Gabriel et al (2020) state that periodic sampling became a dominant strategy for real-time stream processing systems. Although the periodic approach works well, in the distributed environment, one faces such challenges as latency.…”
Section: Literature Surveymentioning
confidence: 99%